Combining ability analysis of rice genotypes for grain yield and related traits under direct-seeded conditions - ZEESHAN ALI; MUHAMMAD NAEEM; IQRA RAFIQ; MUHAMMAD AJMAL; ABD HARIS BAHRUN; ACHMAD KAUTSAR BAHARUDDIN; ANNASTYA NUR FADHILAH; MUHAMMAD FUAD ANSHORI (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Ali Z, Naeem M, Rafiq I, Ajmal M, Bahrun AH, Baharuddin AK, Fadhilah AN, Anshori MF. 2026. Combining ability analysis of rice genotypes for grain yield and related traits under direct-seeded conditions. Biodiversitas 27 (1): d270138. https://doi.org/10.13057/biodiv/d270138. Development of rice toward water scarcity and high input costs encourages a shift toward Direct-Seeded Rice (DSR) systems. Hybrid rice development is one solution to this system's challenge. Therefore, systematic analysis through combining ability is needed to develop hybrid rice on direct-seeded systems. This study aimed to evaluate the combining ability of rice genotypes for grain yield and related traits under DSR conditions. Twenty-seven genotypes from nine parents and 18 F1 crosses were evaluated using Line × Tester design under a Randomized Complete Block Design (RCBD) with three replications during 2023-2024. The results showed that genotype-by-genotype variance for all traits was significant in the analysis of variance. Line 23765 and tester 37768 were good general combiners, while crosses 6723 × 32274, 6728 × 32274, 6880 × 37768, and 7968 × 37667 showed high Specific Combining Ability (SCA) effects. Line 6728 exhibited a significant positive General Combining Ability (GCA) effect for grain yield per plant, while 6723 for grain weight per panicle and number of grains per panicle, indicating yield improvement potential. Both additive and non-additive genetic effects influence trait expression, with non-additive effects being more prominent. This hybrid rice selection process could help develop high-yielding rice varieties under direct-seeded conditions.